1996
DOI: 10.1074/jbc.271.40.24564
|View full text |Cite
|
Sign up to set email alerts
|

Role of Hydrophobic Amino Acids at β85 and β88 in Stabilizing F Helix Conformation of Hemoglobin S

Abstract: Three Hb S variants containing Glu substitutions at Phe-␤85 and/or Leu-␤88 were expressed in yeast in an effort to evaluate the role of hydrophobic amino acids at these sites in stabilizing F helix conformation of Hb S. Helix stability of tetrameric Hb S ␤F85E,␤L88E was measured by CD and compared with those of Hb S ␤F85E, Hb S ␤L88E, Hb A, and Hb S. The CD spectra of these Hb S variants were similar to those of Hb S and Hb A at 10°C. However, changes in ellipticity at 222 nm for Hb S ␤F85E in the CO form at 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

1997
1997
2004
2004

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 16 publications
1
15
0
Order By: Relevance
“…First, the invertase part of the ER-retained hybrid protein is fully active (total invertase activities were almost the same when SEC12-a-f-SUC2 and BETJ-a-f-SUC2 were expressed from the same promoter in the same vector). Results obtained by Reddy and Maley (1990) showed that the active site of invertase is close to the N-terminus and thus not far from the site where invertase was fused to Secl2p. Second, for enzymatic activity of the invertase the assembly into dimers is required (Chu et al, 1983).…”
Section: Discussionmentioning
confidence: 97%
“…First, the invertase part of the ER-retained hybrid protein is fully active (total invertase activities were almost the same when SEC12-a-f-SUC2 and BETJ-a-f-SUC2 were expressed from the same promoter in the same vector). Results obtained by Reddy and Maley (1990) showed that the active site of invertase is close to the N-terminus and thus not far from the site where invertase was fused to Secl2p. Second, for enzymatic activity of the invertase the assembly into dimers is required (Chu et al, 1983).…”
Section: Discussionmentioning
confidence: 97%
“…HNP-1, PG-1 and TP-1 were iodinated by the Iodo-gen or Iodobeads method [13] to a specific activity of 10 &i@g. Trace amounts of radiolabeled HNP-1, PG-1 or TP-1 was incubated with NHS, NHP, and purified Cl subcomponents for 30 min at 37'C. Resulting complexes were followed by native or rate PAGE at pH 5.7 [14] or at pH 8.8 [15]. After electrophoresis toward the anode in a Minigel apparatus (Hoeffer Scientific Instruments, San Francisco, CA) at 4"C, gels were Coomassie stained, dried and exposed to X-OMAT AR films (Eastman Kodak Co., Rochester, NY) at -70°C for l-3 days.…”
Section: Detection Of Defensin Binding In Human Bloodmentioning
confidence: 99%
“…The crystallographic data showed that D86 and E342 were in the proper position and in close contact with the sucrose to represent the catalytic nucleophile and general acid/base catalyst, respectively. Alignments showed that residue E342 is equivalent to the invariant Glu of yeast invertase and Zymomonas mobilis levansucrase (E278), which are vital to catalysis according to site-directed mutagenesis studies [6,7]. Residue D247 was identi¢ed as a transition state stabilizer based on the observation that it forms strong hydrogen bonds with the C3P and C4P hydroxyls of the fructosyl unit, but it is too far away from either the C2P hydroxyl or the glycosidic oxygen to be one of the residues directly involved in catalysis.…”
Section: Introductionmentioning
confidence: 99%